2005
DOI: 10.1097/01.pas.0000162755.84026.9f
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between In Situ Hybridization and Real-time PCR Technique as a Means of Detecting the Integrated Form of Human Papillomavirus 16 in Cervical Neoplasia

Abstract: Integration of the human papillomavirus (HPV) genome is thought to be one of the causes of cancer progression. However, there is controversy concerning the physical status of HPV 16 in premalignant cervical lesions, and there have been no reports on the concordance between detection of the integrated form of HPV16 by real-time PCR and by in situ hybridization. We investigated specimens of cervical intraepithelial neoplasia (CIN) and invasive carcinomas for the physical status of HPV 16 by real-time PCR and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 27 publications
2
39
0
5
Order By: Relevance
“…23,24 All assays were performed using the Chromo 4 DNA Engine cycler (MJ Research, Bio-Rad, CA). Briefly, 20 ll of PCR amplification was done in duplicate contain- ing 100 ng of extracted genomic DNA, 10 ll of 23 TaqMan Universal PCR Master Mix (Applied Biosystems, Foster, CA) and 1 ll of 203 primer/probe.…”
Section: Hpv Viral Load By Real-time Quantitative Pcrmentioning
confidence: 99%
“…23,24 All assays were performed using the Chromo 4 DNA Engine cycler (MJ Research, Bio-Rad, CA). Briefly, 20 ll of PCR amplification was done in duplicate contain- ing 100 ng of extracted genomic DNA, 10 ll of 23 TaqMan Universal PCR Master Mix (Applied Biosystems, Foster, CA) and 1 ll of 203 primer/probe.…”
Section: Hpv Viral Load By Real-time Quantitative Pcrmentioning
confidence: 99%
“…ISH-TSA detected integrated form of HPV16/18 with sensitivity of 70.0% and specificity of 60.9%, as compared with RT-PCR. Fujii et al [22] for 53 women with cervical neoplasia or cervical cancer, compared frequency of HPV16 integrated form in exfoliated cervical cells between RT-PCR and ISH-TSA. They found a concordance rate of 86.0%.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not compare the sensitivity of RT-PCR and ISH-TSA in the assessment of viral genome state. In turn, Fujii et al [22] have shown in cervical neoplasia a strong concordance between RT-PCR and ISH-TSA according to the frequency of HPV16 integration. Therefore, large scale clinical studies are still required to validate the ISH-TSA method [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feyza ve ark.nın yaptığı çalışmada CIn I olgularında %50 integral patern, %27.3 mikst patern, %22.7 epizomal patern saptanmıştır (7). Epizomal HPV-16'nın servikal karsinomlarda rol oynadığı bilinmektedir (8). Epizomal form HPV enfeksiyonu varlığında bile erken dönemlerde sitolojik ve histolojik bulguların negatif olabileceği gösterilmiş, bu nedenle HPV'nin dokuya integrasyonunu göstermede in situ hibridizasyonun PCR yöntemine üstünlüğü vurgulanmıştır.…”
Section: Cın ı Cın ıı Cın ııı Shk N (%) N (%) N (%) N (%)unclassified